Exploring Sorbus torminalis Leaves: Unveiling a Promising Natural Resource for Diverse Chemical and Biological Applications - Gunes, Ak; Enis Fuat, Tüfekci; Ahmed M, Mustafa; Giovanni, Caprioli; Yasemin Celik, Altunoglu; Mehmet Cengiz, Baloglu; Ugur, Cakılcıoglu; Rıdvan, Polat; Ekrem, Darendelioglu; Gokhan, Zengin (Wiley, 2024)
AbstractSorbus torminalis (L.) Crantz has a rich history of versatile applications spanning the fields of medicine and nutrition. It is noteworthy that the decoction obtained from S. torminalis leaves is a traditional treatment method against both diabetes and stomach disorders. Phytochemical profiling determined by HPLC/MS‐MS. The effects of the extracts on cell viability were investigated using the MTT (3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyl tetrazolium bromide) method against MDA‐MB‐231 cell line (human breast adenocarcinoma).The ethanol/water extract contained more concentration of total phenolic (91.41 mg gallic acid (GAE) equivalent /gr) and flavanoid (29.10 mg rutin (RE) equivalent/gr) in the tested extract (p<0.05). Resulting of HPLC analysis, the chemical constituents varied depending on the solvents and chlorogenic acid, hyperoside, isoquercetin, delphindin‐3,5‐diglucoside, procyanidin B2, epicatechin, neochlorogenic acid, 3,5‐dicaffeoylquinic acid were identified in all extracts. Overall, ethanol, n‐hexane and ethyl acetate extracts showed the highest inhibition for the tyrosinase enzyme. The effect of leaf extracts of S. torminalis on antimicrobial, biofilm inhibitory, and anticancer activities was examined. Based on outcomes of our study recognize this plant as a critical source of medically active chemicals for feasible phytopharmaceutical and nutraceutical applications, providing the first scientific insight into the detailed biological and chemical profiles of S. torminalis.
Keywords: Flavonoids; Plant Leaves; Ethanol; Plant Extracts; Phytochemicals; Humans; Sorbus; Antioxidants; 2. Zero hunger; 6. Clean water; 3. Good health